The urgency of rome statute of the international criminal court ratification for republic of Indonesia. - Resa Wilianti (FH 14 UMY 044, 2014)
*44 Rome Statute of the International Criminal Court has been agreed on July 15, 1998 and even though the Statute has entered into force twelve years ago, many democratic nations have not signed or ratified it. This includes Indonesia, along with United State of America, Russia, and other countries. In terms of human rights protection, since year 2000 Indonesia has enacted Law No. 26 of 2000 on Human Rights Court. However, it has not sufficiently uphold human rights enforcement. The National Action Plan for Human Rights of Indonesia, in 2004-2009 stated that the government expects to ratify the Statute in 2008. Truthfully, the target has not been realized, thus in 2009-2014 the government pursues to ratify the Statute in 2013. Indonesia encourage ratifying the Rome Statute of the International Criminal Court in the legislation since there are several serious crimes committed, but the law enforcement enable to investigate exhaustively. Based on the Statute, the court will take the cases from the country, which unwilling and unable to investigate the case of human rights, if the state already ratifies the Statute. The type of this research is a normative legal research with Statute approach and Case approach. By using a qualitative descriptive method, this research will describe the Rome Statute of the International Criminal Court ratification in details related to regulations and conventions especially that related to the Rome Statute of the International Criminal Court. Finally, the result shows the reason why the ratification of Rome Statute of the International Criminal Court for Republic Indonesia is very urgent and important.